A Mitochondrion‐Specific Photoactivatable Fluorescence Turn‐On AIE‐Based Bioprobe for Localization Super‐Resolution Microscope. Issue 25 (2nd May 2016) - Gu, Xinggui; Zhao, Engui; Zhao, Teng; Kang, Miaomiao; Gui, Chen; Lam, Jacky W. Y.; Du, Shengwang; Loy, Michael M. T.; Tang, Ben Zhong
Abstract : A novel mitochondrion‐specific photoactivatable fluorescence turn‐on bioprobe, named as o ‐TPE‐ON+, is designed and readily prepared, operating through a new photoactivatable mechanism of photocyclodehydrogenation. This bioprobe exhibits unique photoactivation behavior in cells, and is applied to super‐resolution imaging of mitochondrion and its dynamic investigation in both fixed and live cells under physiological conditions without any external additives.